Types of Pressure in the Human Body - Kazem Jawad Maleh Fatouh; Noor majeed faraj jalil; Ali Shakir Younis Reda; Murad ali karey Hammoud; Mohammed Ghalib mtasher jazaz (Genius Journals, 2024)
Blood pressure is the force of blood pushing against the walls of blood vessels through which it moves to supply all the body's tissues and organs with food, oxygen, water, and enzymes in what is known as blood circulation. Blood circulation begins with the contraction of the heart muscle to forcefully push all its blood contents, which in turn moves from the heart to the aorta, the largest artery in the human body, and from there to the rest of the arteries. Then the heart relaxes to allow it to be filled with a new amount of blood packed with oxygen, so that it contracts again, pushing a new charge to the aorta. Again, and so on. Medical statistics show the great importance of maintaining blood pressure at an average of 115/75 mmHg, and that exceeding this limit leads to stress on the heart and kidneys, and that high blood pressure may lead to a stroke or early infertility in men.
Keywords: Blood pressure; heart and kidneys; Human Body